MANF: A New Player in the Control of Energy Homeostasis, and Beyond - Yang, Su; Li, Shihua; Li, Xiao-Jiang (Frontiers in Physiology, 2018)
All human behaviors, including the control of energy homeostasis, are ultimately mediated by neuronal activities in the brain. Neurotrophic factors represent a protein family that plays important roles in regulating neuronal development, function, and survival. It has been well established that canonical neurotrophic factors, such as brain-derived neurotrophic factor (BDNF) and ciliary neurotrophic factor (CNTF), play important roles in the central regulation of energy homeostasis. Recently, a class of noncanonical neurotrophic factors, represented by mesencephalic astrocyte-derived neurotrophic factor (MANF), has been discovered. MANF is structurally and functionally distinct from those canonical neurotrophic factors, hence raising an issue of whether it can be considered as a neurotrophic factor. Nonetheless, emerging evidence suggests that MANF is critically involved in many neuronal activities. Here, we review our current understanding about the functions of MANF in the brain, with a primary focus on the control of energy homeostasis.